Effects of a Modified German Volume Training Program on Muscular Hypertrophy and Strength. Issue 11 (November 2017) - Amirthalingam, Theban; Mavros, Yorgi; Wilson, Guy C.; Clarke, Jillian L.; Mitchell, Lachlan; Hackett, Daniel A.
Abstract : Abstract: Amirthalingam, T, Mavros, Y, Wilson, GC, Clarke, JL, Mitchell, L, and Hackett, DA. Effects of a modified German volume training program on muscular hypertrophy and strength. J Strength Cond Res 31(11): 3109–3119, 2017—German Volume Training (GVT), or the 10 sets method, has been used for decades by weightlifters to increase muscle mass. To date, no study has directly examined the training adaptations after GVT. The purpose of this study was to investigate the effect of a modified GVT intervention on muscular hypertrophy and strength. Nineteen healthy men were randomly assign to 6 weeks of 10 or 5 sets of 10 repetitions for specific compound resistance exercises included in a split routine performed 3 times per week. Total and regional lean body mass, muscle thickness, and muscle strength were measured before and after the training program. Across groups, there were significant increases in lean body mass measures, however, greater increases in trunk ( p = 0.043; effect size [ES] = −0.21) and arm ( p = 0.083; ES = −0.25) lean body mass favored the 5-SET group. No significant increases were found for leg lean body mass or measures of muscle thickness across groups. Significant increases were found across groups for muscular strength, with greater increases in the 5-SET group for bench press ( p = 0.014; ES = −0.43) and lat pull-down ( p = 0.003; ES = −0.54). It seems that the modified GVT program is no more effective than performing 5 sets per exercise for increasing muscle hypertrophy and strength. To maximize hypertrophic training effects, it is recommended that 4–6 sets per exercise be performed, as it seems gains will plateau beyond this set range and may even regress due to overtraining.